2020
DOI: 10.1007/978-3-030-59354-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Residual Embedding Similarity-Based Network Selection for Predicting Brain Network Evolution Trajectory from a Single Observation

Abstract: Predicting the evolution trajectories of brain data from a baseline timepoint is a challenging task in the fields of neuroscience and neuro-disorders. While existing predictive frameworks are able to handle Euclidean structured data (i.e, brain images), they might fail to generalize to geometric non-Euclidean data such as brain networks. Recently, a seminal brain network evolution prediction framework was introduced capitalizing on learning how to select the most similar training network samples at baseline to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Models that foresee the evolution of brain connectivity from a single baseline graph can be especially useful for both scientific discovery and clinical decisionmaking (23,24). Therefore, prior works proposed different GNN-based architectures that can be divided into two families: dichotomized learning-based models (47,48) and end-toend learning-based models (46). These works aim to produce a trajectory either represented with one brain graph such as predicting brain connectivities of an Alzheimer's disease patient at 9-month after first scans or multiple follow-up brain graphs acquired at different timepoints (Figure 2-C).…”
Section: Cross-time Graph Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models that foresee the evolution of brain connectivity from a single baseline graph can be especially useful for both scientific discovery and clinical decisionmaking (23,24). Therefore, prior works proposed different GNN-based architectures that can be divided into two families: dichotomized learning-based models (47,48) and end-toend learning-based models (46). These works aim to produce a trajectory either represented with one brain graph such as predicting brain connectivities of an Alzheimer's disease patient at 9-month after first scans or multiple follow-up brain graphs acquired at different timepoints (Figure 2-C).…”
Section: Cross-time Graph Predictionmentioning
confidence: 99%
“…Challenges and insights. Although (47,48) methods can reliably predict the future brain connectivities, their performance is still less promising since their dichotomized learning strategy limits the scalability to predict jointly the follow-up brain graphs. Even though ( 46) is an end-to-end learning framework, it is still based on the edge convolution operation which hinders its scalability in terms of training time when applied on large-scale graphs.…”
Section: Cross-time Graph Predictionmentioning
confidence: 99%
“…By construction, triangular meshes are undirected graphs, with analogous edges, and their intersections are interpreted as vertices. Several studies (Bessadok and Rekik, 2018;Fornito et al, 2015;Göktaş et al, 2020;Gurbuz and Rekik, 2020;Nebli and Rekik, 2020;Yang et al, 2020) have demonstrated that graphs derived from different types of brain-related connectivity, functional or structural, are more robust in accuracy and computation time, versus traditional neuroimaging methods.…”
Section: Spectral Graph Convolution (Chebynets)mentioning
confidence: 99%